Las TIC's como herramienta de investigación científica - Corredor Acosta, Andrea; Sandino León, Martín (Góndola, enseñanza y aprendizaje de las ciencias, 2009)
In this paper, we discuss the importance of ICTs in researchers work when they are looking for new knowledge. We found that researchers consider important to seek new tools and identify their potential to take them as the basis of their research, for example for the classification and compilation of bibliography and data. For this purpose, we conducted a survey of a community of research professors and undergraduate students of last year of Physics and then analyzed the results to see the importance and usefulness of ICTs in the development of science.